2017
DOI: 10.1021/acs.chemmater.6b04563
|View full text |Cite
|
Sign up to set email alerts
|

Functional Acid and Base Hybrid Catalysts Organized by Associated (Organo)aluminosilicate Layers for C–C Bond Forming Reactions and Tandem Processes

Abstract: Novel bifunctional acid-base monolayered hybrid catalysts (MLHMs), based on associated individual (organo)aluminosilicate sheets with amino and sulfonic pending groups located in the interlayer space, have been successfully prepared by direct alkaline hydrothermal synthesis and evaluated in consecutive catalytic transformations. Different characterization techniques such as chemical and thermogravimetrical analyses, X-ray diffraction, TEM microscopy, nuclear magnetic resonance (NMR), temperature programmed des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
(140 reference statements)
0
18
0
Order By: Relevance
“…Metal–organic frameworks (MOFs) are a class of crystalline materials with high surface areas and well‐defined pore systems that hold promise for uses as adsorbents and membranes . The ability to tune their composition also provides opportunities in heterogeneous catalysis, especially when bifunctional catalysts are desirable, such as in the catalysis of tandem reactions . One such reaction is the isomerization of glucose to fructose in the presence of alcohols .…”
Section: Methodsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are a class of crystalline materials with high surface areas and well‐defined pore systems that hold promise for uses as adsorbents and membranes . The ability to tune their composition also provides opportunities in heterogeneous catalysis, especially when bifunctional catalysts are desirable, such as in the catalysis of tandem reactions . One such reaction is the isomerization of glucose to fructose in the presence of alcohols .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Thea bility to tune their composition also provides opportunities in heterogeneous catalysis,e specially when bifunctional catalysts are desirable,s uch as in the catalysis of tandem reactions. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] One such reaction is the isomerization of glucose to fructose in the presence of alcohols. [27][28][29][30] First proposed by Saravanamurugan et al, [27] it has been shown to be ah igh-yield route to fructose and apromising alternative to aqueous routes.F or instance,when glucose isomerization to fructose is combined with fructose ketalization, increased fructose yields beyond the equilibrium levels are achievable and the obtained fructoside is readily hydrolyzed to fructose upon addition of water (Scheme 1).…”
mentioning
confidence: 99%
“…The hydrothermal processes were later extended to the synthesis of bifunctional acid-base hybrid materials based on ordered organic aluminosilicate sheets with amino and sulfonic groups located in the interlayer space. 114 The as-prepared materials proved efficient as heterogeneous acid, base or even as acid/ base catalysts in a diverse set of reactions, including Henry reactions, acetalization reactions and even a one-pot two-step reaction that involved acetal hydrolysis followed by Knoevenagel condensation.…”
Section: Layered Metal Silicatesmentioning
confidence: 99%